Transmembrane protein TMEM119 facilitates the stemness of breast cancer cells by activating Wnt/β-catenin pathway. Issue 1 (1st January 2021) - Yang, Ben; Wang, Fengling; Zheng, Gang
ABSTRACT: The effects of transmembrane protein 119 (TMEM119) on breast cancer progression have not been elucidated. This study aims to investigate the roles of TMEM119 in breast cancer progression. Clinical samples and online datasets were used to determine TMEM119 expression and its correlation between patients' survival. Wound healing, transwell invasion, mammary spheroid formation, and ALDH activity were performed to detect the effects of TMEM119. RNA-sequencing, Luciferase report analysis, Co-IP, and ChIP analysis were constructed to reveal the underlying mechanisms. We found that TMEM119 was highly expressed in breast cancer tissues and cells compared to that in normal tissues and cells. Additionally, TMEM119 expression was negatively correlated with the survival of breast cancer patients. TMEM119 knockdown reduced the expression of stemness markers, mammary spheroid-formation ability and ALDH activity. RNA-sequencing analysis indicated that Wnt/β-catenin signaling was enriched in cells with TMEM119 overexpression. Further co-IP experiments indicated that TMEM119 interacted with β-catenin and maintained its protein stability. Conversely, β-catenin directly bound to TMEM119 gene promoter and thus increased TMEM119 transcriptional activity and its expression. Finally, we demonstrated that TMEM119-mediated effects depended on Wnt/β-catenin signaling. Thus, this work reveals a novel TMEM119-β-catenin positive feedback loop essential for breast cancer cell stemness.